Pulmonary tuberculosis as a confounder for bronchogenic carcinoma due to delayed and misdiagnosis - Agrawal, A; Agarwal, P K; Tandon, R; Singh, S; Singh, L; Sharma, S (Indian Journal of Community Health, 2013)
Background: There are many similarities between lung cancer and tuberculosis as both are common and present with almost similar symptoms and radiological findings, a large number of lung cancer patients treated for tuberculosis initially and that leads delay in diagnosis and progression of disease. Aim: In this present study we intend to find out the impact of past and present tuberculosis on the diagnosis and treatment of lung cancer. Results: Out of 195 diagnosed cases of bronchogenic carcinoma, 79 (40%) were taking anti-tubercular therapy for at least 1 month duration (range 1 month- 12 months). Fifty one (26%) patients had received ATT in past. Twenty six patients (12.5%) were found to have co-existent tuberculosis and lung cancer, only 18 patients were newly diagnosed and the remaining were relapse cases. Mean delay for diagnosis of lung cancer in patients who were taking ATT inadvertently, owing to wrong diagnosis, was 3.2 months (range 1 month to 12 months). Conclusion: We found that large numbers of the bronchogenic carcinoma patients were misdiagnosed as a case of tuberculosis, this leads to significant delay in diagnosis and progression of cancer and results in poor outcome and lower survival. We recommend an early search for malignancy in suspected tubercular patients having risk factors for bronchogenic carcinoma. Moreover sputum negativity for AFB and poor response to empirical anti-tubercular therapy in these setting should arouse suspicion for malignancy.